(3TQM dGejI GdYLes - (3eMeO Hf YeQ Hf eHGQc GdMVQei GdTGaYjs; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdbUjOI GdaQjOI GdeTghQI HdGejI GdYLe , GdLGeYg ddCeKGd GdSGFQ hGdMce s
(3BNQgG (B:s
(3aGLgO faSc hGSJced aVGFdgG aCfJ HGdfaS dG HGdLSe EfSGf fSCd Gddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HBNQgG fbhd TYQjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdQGHYI HGNJdGa ai HYV GdYHGQGJ hGdCdaGXs
(3cJH GdTYQ HGdMeQI s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs